2021
DOI: 10.1109/access.2021.3092970
|View full text |Cite
|
Sign up to set email alerts
|

COVID19-Routes: A Safe Pedestrian Navigation Service

Abstract: COVID-19 has become a global pandemic during 2020 due to its high contagiousness and the high mobility of the world's population today. In just one year, this virus has caused millions of infections and deaths worldwide. These numbers will continue to grow until the population becomes immune to the virus thanks to an effective vaccine. Until this is possible, the only viable strategy is to try to stop its expansion through preventive measures such as limiting mobility, the use of masks, etc. In order to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In Table 1, we examine recent studies investigating the navigation and route recommendation for users while exploiting the IoT data to help on mitigating the spread of infection, especially COVID-19 [26]- [30]. We found that majority of selected studies focus exclusively on indoor navigation, while the other concern only on out-door navigation.…”
Section: Related Workmentioning
confidence: 99%
“…In Table 1, we examine recent studies investigating the navigation and route recommendation for users while exploiting the IoT data to help on mitigating the spread of infection, especially COVID-19 [26]- [30]. We found that majority of selected studies focus exclusively on indoor navigation, while the other concern only on out-door navigation.…”
Section: Related Workmentioning
confidence: 99%
“…SARS-CoV-2 or COVID-19 is the worldwide epidemic caused by Coronavirus illness in 2019 caused severe acute respiratory syndrome (SARS) and was found for the first time in Wuhan, which is located in China. In March 2020, the World Health Organization (WHO) gave the disease the name COVID-19 and predicted that it would spread over the world as an epidemic (Cantarero et al 2021;De Anda-Suarez et al 2022). COVID-19 negatively affects the health of people, especially the elderly, people with existing medical issues, and people whose immune systems are already impaired.…”
Section: Introduction 11 Overviewmentioning
confidence: 99%